The interactive effects of soil transplant into colder regions and cropping on soil microbiology and biogeochemistry - Shanshan Liu; Feng Wang; Kai Xue; Bo Sun; Yuguang Zhang; Zhili He; Joy D. Van Nostrand; Jizhong Zhou; Yunfeng Yang (Environmental Microbiology, 2015)
Summary Soil transplant into warmer regions has been shown to alter soil microbiology. In contrast, little is known about the effects of soil transplant into colder regions, albeit that climate cooling has solicited attention in recent years. To address this question, we transplanted bare fallow soil over large transects from southern C hina (subtropical climate zone) to central (warm temperate climate zone) and northern C hina (cold temperate climate zone). After an adaptation period of 4 years, soil nitrogen components, microbial biomass and community structures were altered. However, the effects of soil transplant on microbial communities were dampened by maize cropping, unveiling a negative interaction between cropping and transplant. Further statistical analyses with Canonical correspondence analysis and Mantel tests unveiled annual average temperature, relative humidity, aboveground biomass, soil pH and NH 4 + ‐ N content as environmental attributes closely correlated with microbial functional structures. In addition, average abundances of amoA ‐ AOA (ammonia‐oxidizing archaea) and amoA ‐ AOB (ammonia‐oxidizing bacteria) genes were significantly ( P AOA and AOB contributed to the soil functional process of nitrification. These results suggested that the soil nitrogen cycle was intimately linked with microbial community structure, and both were subjected to disturbance by soil transplant to colder regions and plant cropping.